Prediction of Stall Phenomenon in Blade-to-Blade Passage of Axial Flow Compressor - Arkan K. Al-Taie; Abbas Abdul-Hussein (Engineering and Technology Journal, 2009)
The flow field between two blades was analyzed numerically by solving thesteady, two dimensional and incompressible (time-mass averaged Navier- Stokesequations). The (κ-ε) turbulent model was used to simulate the condition of themomentum equation and to obtain the eddy viscosity. The SIMPLE algorithm isused to satisfy velocity-pressure coupling method and to satisfy the conservationof mass. A computer code was constructed in this work using FORTRAN 90language to simulate the flow. The numerical results were compared withexperimental results of other researcher for flow through the cascade of axialcompressor, and were found to be in a good agreement. Three different airfoilscommon, used for axial flow compressors blades, were investigated in the presentstudy. The study shows that stall happens. At incidence angles (-80 to 70) forNACA 65(12)10 and (-90 to 30) for NACA 65(18)10 and (-70 to 90) for NACA65(8)10. The result also show that stall happens when the total pressure loss isgreater than 0.06 for NACA 65(8)10 when stagger angle is greater than 450 stallhappens for total pressure loss less 0.06 as the outlet flow angle decreases.However, the quasi-three dimensional, steady, incompressible, turbulent, adiabaticand single-phase fluid flow inside the blade-to-blade passage of an axial flowcompressor stator was also studied and the study shows that Stall was seen to takeplace at blade tips during starting.